Floristic composition and phytodiversity status of Sitakunda Ecopark, Chittagong, Bangladesh - Islam, Md Anwarul; Rahman, Mohammad Mahfuzur; Hossain, Gazi Mosharof (Jahangirnagar University Journal of Biological Sciences, 2016)
The present study dealt with the exploration and documentation of the floristic composition and phyto-diversity of Sitakunda Eco-park, Chittagong, Bangladesh. A total of 412 vascular plant species under 315 genera belonging to 94 plant families have been recorded from the study area during February, 2013 to April, 2015. Out of these recorded taxa, 330 were dicotyledons, 62 were monocotyledons, 5 were gymnosperms and 15 were pteridophytes. Among those, the maximum 144 species belonged to herbs followed by 138, 75 and 55 species as trees, shrubs and climbers, respectively. The species composition among the plant families varied in plant groups. In dicotyledonous group, Euphorbiaceae appeared to be the largest family with 35 species, whereas Poaceae showed the largest family containing 30 species among monocotyledonous group. The highest values of both Shannon-Weiner and Simpson diversity indices have been observed as 3.82 and 0.98, respectively to site D during monsoon season, whereas the lowest values 3.19 and 0.95, respectively of these indices were recorded in site A during summer season. Jahangirnagar University J. Biol. Sci. 5(1): 29-45, 2016 (June)